CORRELATION OF PUBLIC-LEGAL AND PRIVATE-LEGAL METHODS OF REGULATION - Schramm, Ханс-Йоахим (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
This research was prepared by agreement with the State Institution «The Institute of Legislation of the Republic of Kazakhstan» and it is of an informational and analytical nature. The author of the research is a Professor, Doctor of law Hans-Joachim Schramm, managing director of the Institute of Eastern Law at the University of the German city of Wismar. Since 1996, the researcher has been involved in numerous legal reform projects in the CIS countries through the German organizations GIZ and IRZ. Along with that he co-authored the book «Civil Law of the South Caucasus and Central Asia» in conjunction with Professor Rolf Knipper and Lado Chanturia. In the research the author made an attempt to analyze the correlation of public-law and private-law methods of regulating public relations in order to determine approaches to the implementation of subsection 2.4 of section 2 of the Concept of the legal policy of the Republic of Kazakhstan for the period from 2010 to 2020, approved by the Decree of the President of the Republic of Kazakhstan dated August 24, 2009 No. 858. According to the approach chosen by the author, the task of elaboration of the correlation of public-law and private-law methods of regulation issues requires, first of all, clarifications. Since the issue of legal relations regulation covers the entire legal system of the Republic of Kazakhstan, the task of this limited-volume research can not be considered as a systematic consideration of all legislative acts in this aspect. In the context of this analysis, it can only be about developing criteria for distinguishing regulatory methods with examples, on the basis of which individual legislative acts will be further investigated. The presented research is consistently published in two issues of the Bulletin of the Institute of Legislation of the Republic of Kazakhstan, with the content divided into two parts. Thus, in this part the following range of questions is presented to the attention of readers: - principles of public law (administrative law) in contrast to the principles of private law; - the interaction of public law and private law regulatory methods; - the meaning of the distinction between public and private law for the regulation of property law.